Analisis Perencanaan Dan Pertanggungjawaban Pengelolaan APBDES Di Desa Medangasem Dan Ciptamarga Kecamatan Jayakerta Kabupaten Karawang - Rika Nurfadilah; Isro’iyatul Mubarokah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this analysis is to analyze and explain the planning and accountability of APBDes management in Medangasem and Ciptamrga villages and their compliance with applicable regulations. The research method used in this research is descriptive with a qualitative approach. The data used in this study are primary and secondary, data collection using interview techniques and document studies. The results of this study indicate that the planning and accountability carried out by the village of Medangasem and the village of Ciptamarga are in accordance with Permendagri Number 20 of 2018 but based on the principles that apply to this regulation, namely the principle of transparency, Ciptamarga Village is more transparent than Medangasem Village. In the allocation of the use of the Medangasem and Ciptamarga village budgets in 2018-2019 the Medangasem village is in accordance with Government Regulation Number 43 of 2014 while the Ciptamrga village is not yet appropriate. However, in 2020 the allocation of the Medangasep and Ciptamarga village budgets was not in accordance with government regulation No. 43 of 2014 because the total allocation for the use of the budget for development, coaching, and empowerment was less than the maximum limit of 70%. This is due to the handling and prevention of COVID-19.